The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1589/jpts.28.2519
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of abdominal muscle thickness according to feedback method used during abdominal hollowing exercise

Abstract: [Purpose] This study was intended to examine the most effective feedback method for contracting the musculus transversus abdominis muscle by using basic training, a pressure biofeedback unit, and real-time ultrasonographic imaging during abdominal hollowing exercise training. [Subjects and Methods] The subjects in this study were 30 healthy young students in their twenties. Thirty subjects were divided randomly and equally into the basic training, the pressure biofeedback unit, and real-time ultrasonographic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 14 publications
(14 reference statements)
2
21
1
Order By: Relevance
“…This was supported by the study of McMeekan et al [19], which showed an excellent correlation between the activity and thickness of the TrA. In addition, Lee and colleagues [15] reported that ADIM training with the feedback method (i.e. ultrasound imaging and PBU) for 15 minutes resulted in significantly thicker TrA muscle than using manual contact.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This was supported by the study of McMeekan et al [19], which showed an excellent correlation between the activity and thickness of the TrA. In addition, Lee and colleagues [15] reported that ADIM training with the feedback method (i.e. ultrasound imaging and PBU) for 15 minutes resulted in significantly thicker TrA muscle than using manual contact.…”
Section: Discussionmentioning
confidence: 71%
“…EMG is an invasive method that is limited in its adoption [19]. Lee and colleagues [15] compared the effectiveness of three feedback methods (i.e. ultrasonography, PBU, and palpation) for contracting the TrA muscle and found that using visual feedback was more effective than only palpation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the search and selection process (identification, screening, eligibility and analyzed) from the 1084 studies identified in the search to the 11 studies included in the review [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] are described in the flow diagram shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies showed an overall low risk of bias [ 22 , 23 , 24 , 27 , 28 , 30 , 31 ]. However, four studies presented some concerns regarding the measurement of the outcomes and the reported results which should be considered on data interpretation [ 25 , 26 , 29 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation